A Model of Cube-Sat - Silwal, Abhishek; Ghimire, Abhishek; Khanal, Kapalik; Ghimire, Umesh Kanta (Journal of Innovations in Engineering Education, 2020)
Weather satellite is a type of satellite which is mainly used for the monitoring of the weather and climate of the Earth. This project purposes the creation of a working model of weather cube-sat, a weather Pico-satellite to monitor the condition of a small geographical area and determine its weather conditions and pollution level. Various sensors like temperature, barometric, humidity, dust and lux intensity sensors as well as a rain detector is used to measure the corresponding physical quantities and situations for this purpose. This system uses nRF transceivers for the transmission of data from the cube-sat to the ground station. Even though it is not included in our project, it is also possible to forecast the weather for the area based on previous values measured from the system. For the validation of the project, the measured data were compared with each other as well as the corresponding values of the physical quantities measured from other devices to check for its consistency and accuracy.